A Human Umbilical Cord Mesenchymal Stem Cell-Conditioned Medium/Chitosan/Collagen/β-Glycerophosphate Thermosensitive Hydrogel Promotes Burn Injury Healing in Mice. (2nd December 2019) - Zhou, Panpan; Li, Xue; Zhang, Bing; Shi, Qing; Li, Dong; Ju, Xiuli
Abstract : We investigated the effects of a human umbilical cord mesenchymal stem cell-conditioned medium (MSC-CM)/chitosan/collagen/ β -glycerophosphate ( β -GP) thermosensitive hydrogel (MSC-CM/hydrogel) on mice with third-degree burns. MSC-CM was collected and mixed with chitosan, collagen, and β -GP to generate the thermosensitive MSC-CM/hydrogel, which was stored in the liquid phase at 4°C. The wounds of established third-degree burned mice were then externally covered with the MSC-CM/hydrogel, which formed a gel when placed on the wounds at physiological temperature. Injured mice in three additional groups were treated with unconditioned MSC medium (UM), MSC-CM, or UM/chitosan/collagen/ β -GP thermosensitive hydrogels. Skin wound samples were obtained 4, 14, and 28 days after burning for further analysis by hematoxylin and eosin and Ki-67 staining. Wound healing rates and times, in addition to immunohistochemical results, were then compared and analyzed among the four groups. Application of the MSC-CM/hydrogel shortened healing time, limited the area of inflammation, enhanced reepithelialization, promoted the formation of high-quality, well-vascularized granulation tissue, and attenuated the formation of fibrotic and hypertrophic scar tissue. In summary, MSC-CM/hydrogel effectively promotes wound healing in third-degree burned mice.